Ant based probabilistic routing with pheromone and antipheromone mechanisms - Sandalidis, Harilaos G.; Mavromoustakis, Constandinos X.; Stavroulakis, Peter (My University, 2004)
Using the idea of probabilistic routing, calls in an ant based decentralized scheme are not routed according to the largest probabilities in the pheromone tables but randomly according to these probabilities. This principle can be particularly helpful in order to further minimize possible node congestion problems. An additional incorporation of the antipheromone mechanism in the operation of artificial ants helps in better biasing the network. This paper examines the behaviour of such a routing scheme using a proper set of suitable metrics.
Keywords: Adaptive routing; Ant system; Probabilistic routing; Pheromone and antipheromone principles